Rebel at work : how to innovate and drive results when you aren't the boss - Neelan, Natalie (Tantor Media, 2018)
Are you tired of leadership that claims to want an innovative culture but in fact throws up internal roadblocks against any new initiatives' If you're a frustrated employee banging your head up against the same brick wall, then Rebel at Work is the book for you. The problem with bestselling leadership, innovation, and business books on the market is that they are written for executive leadership. Rebel at Work is for the employee who does the actual work. Change only happens from the inside out. It happens when valuable employees get fed up with leadership's vague direction and conflicting priorities. Rebel at Work will allow you to finally take matters into your own hands. You'll learn:- How to understand the unwritten rules in your organization-so you can work around them;- The types of corporate conformists, as well as their hardwiring-so you can mitigate their fear of change;- How jargon kills promising ideas, and how to bring clarity to all conversations;- And how to prepare step-by-step plans that increase your chances for buy-in by your leadership.